On the statistical mechanics of an adiabatic ensemble - Andreev, S.N.; Rukhadze, A.A.; Samokhin, A.A. (Condensed Matter Physics, 2004)
Different descriptions of an adiabatic process based on statistical thermodynamics and statistical mechanics are discussed. Equality of the so-called adiabatic and isolated susceptibilities and its generalization as well as adiabatic invariants are essentially used to describe adiabatic processes in the framework of quantum and classical statistical mechanics. It is shown that distribution function in adiabatic ensemble differs from a quasi-equilibrium canonical form provided the heat capacity of the system is not constant in adiabatic process.